Association between behavioural biases and investment decision-making: a meta-analysis - Lim, Swee Hoe (Nanyang Technological University, 2022)
Making sound investment decisions is not easy, and the field of behavioural finance warns of behavioural biases to avoid. While studies examining the relationships between behavioural biases and investment decision-making are aplenty, efforts to consolidate and analyse them collectively are scarce. Therefore, this meta-analysis aims to investigate the relationship between seven of the most prominent behavioural biases – as identified by past literature – present among individual investors and two aspects of investment decision-making, intuitive and rational. These seven biases were identified as overconfidence, herding, representativeness, availability, anchoring and adjustment, disposition effect and loss aversion. In total, 86 effect sizes from 36 studies comprising 7,615 participants from eight countries were analysed in a correlational meta-analysis. The findings show that overconfidence, representativeness, availability, and anchoring and adjustment biases were significantly and positively associated with the intuitive aspect of investment decision-making while loss aversion and disposition effects were significantly and positively associated with the rational aspect of investment decision-making. Herding was found to be not associated with both aspects of investment decision-making. Among the seven moderators examined, only age significantly moderated the relationship between availability bias and the intuitive aspect of investment decision-making, and the relationship between loss aversion bias and the rational aspect of investment decision-making. Gender, investing experience, education, continental difference, sampling technique and publication status did not display any significant moderation effects. The limitations of the present study as well as the implications for future research and practice are also discussed.